2011
DOI: 10.5455/cap.20110324
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and Related Variables

Abstract: ÖZETİnsanların kendileri için önemli gördükleri kişilere karşı geliştirdikleri güçlü duygusal bağlar olarak tanımlanan bağlanma, uzun yıllardır araştırmacılar tarafından incelenmektedir. Bağlanma kuramı, yaşamın ilk yıllarında oluştu-rulan bağlanma örüntülerinin içsel çalışan modeller aracılığıyla yaşamın daha sonraki dönemlerine pek fazla değişime uğramadan aktarıldığını ileri sürer. Bununla beraber bağlanma örüntülerinin bireylerin sosyal-duygusal yeterliliklerini belirlemede önemli bir yere sahip olduğu düş… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
(73 reference statements)
0
5
0
3
Order By: Relevance
“…When securely attached adolescents need help, they ask help from their families or friends. Thus, one can argue that securely attached adolescents act with more functional coping strategies (Morsünbül & Çok, 2011). On the other hand, non-securely attached adolescents are oriented towards risky behaviors in crisis situations, as opposed to functional coping strategies (Cooper et al, 1998).…”
Section: Results Discussion and Recommendationsmentioning
confidence: 99%
“…When securely attached adolescents need help, they ask help from their families or friends. Thus, one can argue that securely attached adolescents act with more functional coping strategies (Morsünbül & Çok, 2011). On the other hand, non-securely attached adolescents are oriented towards risky behaviors in crisis situations, as opposed to functional coping strategies (Cooper et al, 1998).…”
Section: Results Discussion and Recommendationsmentioning
confidence: 99%
“…Prenatal bağlanma, zaman içinde gelişen, özel eşsiz bir ilişkidir. Anne-bebek bağlanma süreci gebelik, doğum ve postpartum periyod süresince gelişir (12,13).…”
unclassified
“…Marital adjustment is acknowledged as one of the most important factors that affect the attachment process (3,5,7). While any adjustment disorders weaken the relationship between parents, it could also affect the relationship between the father and the infant, whose need for care from a mother is a must particularly in the first years (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Length of marriage duration affects marital adjustment (3,18,22). This study found that fathers with longer marriage durations demonstrate higher paternal-infant attachment levels.…”
Section: Discussionmentioning
confidence: 99%